863Alcohol and cancer in an Australian cohort of 226, 162 participants aged 45 years and over. (2nd September 2021) - Sarich, Peter; Canfell, Karen; Egger, Sam; Banks, Emily; Joshy, Grace; Grogan, Paul; Beral, Valerie; Weber, Marianne
Abstract: Background: Australia has a relatively high level of alcohol consumption. Although alcohol consumption is known to increase the risk of several cancer types internationally, local evidence for Australia is limited. Methods: Cox proportional hazards regressions were used to calculate hazard ratios (HR) and 95% confidence intervals (CI) for cancer risk in relation to weekly alcohol consumption among 226, 162 participants aged ≥45 years (2006-2009) in the 45 and Up Study, an Australian prospective cohort study. Incident cancer cases were ascertained by linkage to the New South Wales Cancer Registry to December 2013 by the Centre for Health Record Linkage. Results: Over a median 5.4 years, 17, 332 cancers were diagnosed. Increasing levels of alcohol intake were associated with increased risk of any cancer (HR per seven drink increase in weekly consumption: 1.02; 95% CI: 1.00-1.04), and cancers of the upper aerodigestive tract (1.19;1.10-1.29), mouth/pharynx (1.18;1.08-1.29), oesophagus (1.22;1.04-1.43), colorectum (1.09;1.04-1.15), colon (1.13;1.06-1.20), liver (1.22;1.04-1.44), breast (1.09;1.00-1.18), and melanoma (1.05;1.00-1.10); whereas an inverse association was observed for thyroid cancer (0.80;0.64-1.00). We estimated that by age 85 years, Australian men and women who consume >14 drinks/week increase their absolute risk of alcohol-attributable cancer by 4.4% and 5.4%, respectively, compared to non-drinkers. Conclusions: We report relative risks of cancer incidence in relation to alcohol consumption that match the international evidence. In Australia, a nation with relatively high alcohol consumption, these risks may translate into a significant public health burden. Key messages: We have generated estimates for the relationship between alcohol consumption and cancer risk in Australia.